The Perspective of PPKn Lecturers at PGRI Wiranegara University on the Formation of Pancasila Moral Character among PPKn Students at PGRI Wiranegara University in the Implementation of Classroom Learning - Cicilia Nur Anugrah; Intan Firdatul Firdaus Mardianti; Rentika Najwa Aulia (Insan Akademika Publications, 2025)
Forming the moral character of Pancasila is about how a person behaves and acts in his or her life. This means building, developing, and teaching someone to have good thoughts, be noble in heart, and behave or act according to the values or philosophies contained in Pancasila. How lecturers teach in the lecture curriculum shows that education plays an important role in the formation of student character. Good character formation is the process of character formation by considering the moral value of Pancasila. Pancasila, which is the ideology and foundation of the nation state of Indonesia, can be defined as the moral of Pancasila. Nowadays, the many cultures that enter are a challenge for the nation's morals, especially for students. The decline in morals in accordance with Pancasila values ​​in students must receive full attention, especially from lecturers as educators in the campus environment. The purpose of this study is to determine the perception of lecturers about students' Pancasila morals, as well as how to form students' characters during lecture learning. So the main focus in this study is the perception of lecturers about the formation of students' moral character, the implementation of student morals and the perception of lecturers towards Pancasila moral character. In collecting data for this article research, the author used a qualitative method by interviewing PPKn lecturers at PGRI Wiranegara University. So the results of the research in this article are, Pancasila moral character is a character and morals that are in accordance with Pancasila values ​​and students' moral character cannot be seen only from when they are in lectures, but must also be seen from how they behave in the midst of society. This article has important implications in the formation of Pancasila moral character in students.